2021
DOI: 10.1111/jth.15517
|View full text |Cite
|
Sign up to set email alerts
|

Association of prehospital antiplatelet therapy with survival in patients hospitalized with COVID‐19: A propensity score‐matched analysis

Abstract: Purpose: Coronavirus disease 2019 (COVID-19) is associated with hypercoagulability and increased thrombotic risk. The impact of prehospital antiplatelet therapy on inhospital mortality is uncertain. Methods:This was an observational cohort study of 34 675 patients ≥50 years old from 90 health systems in the United States. Patients were hospitalized with laboratory-confirmed COVID-19 between February 2020 and September 2020. For all patients, the propensity to receive prehospital antiplatelet therapy was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Investigations of antiplatelet therapies outside of aspirin alone do not consistently demonstrate improved patient outcomes and were nevertheless largely dominated by aspirin therapy. A large study of nearly 35,000 patients ≥50 years old demonstrated improved benefits for those taking antiplatelet therapy prehospital to those who did not for in-hospital mortality (18.9% vs. 21.5%, p < 0.001) and a 2.6% absolute reduction in mortality (HR 0.81, 95% CI 0.76–0.87, p < 0.005) [ 97 ]. However, most patients were taking aspirin (83.9%), with less on clopidogrel (8.2%), dual antiplatelet therapy (7.4%), or ticagrelor or prasugrel, and the authors did not break down differences between therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of antiplatelet therapies outside of aspirin alone do not consistently demonstrate improved patient outcomes and were nevertheless largely dominated by aspirin therapy. A large study of nearly 35,000 patients ≥50 years old demonstrated improved benefits for those taking antiplatelet therapy prehospital to those who did not for in-hospital mortality (18.9% vs. 21.5%, p < 0.001) and a 2.6% absolute reduction in mortality (HR 0.81, 95% CI 0.76–0.87, p < 0.005) [ 97 ]. However, most patients were taking aspirin (83.9%), with less on clopidogrel (8.2%), dual antiplatelet therapy (7.4%), or ticagrelor or prasugrel, and the authors did not break down differences between therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the role of the direct oral anticoagulants have also not shown any evidence of a survival benefit to date or of a disease-modifying effect [ 31 ]. Initial observational data suggested that anti-platelet therapy might be beneficial in COVID-19 although no survival advantage or reduction in disease severity was detected in a recent randomised controlled trial, although the outcomes from other additional studies are also awaited [ 32 , 33 ].…”
Section: Anticoagulant Therapy As a Treatment Modality For Covid-19: Unanswered Questionsmentioning
confidence: 99%
“…Indeed, clinical studies of anti-platelet therapy in COVID-19 demonstrated that aspirin is the only anti-platelet drug that can significantly affect patient's condition [14]. On the other hand, other studies demonstrated that pre-hospitalization antiplatelet therapy can significantly decrease the mortality from COVID-19 [15]. Platelet dysfunction in COVID-19 has been shown several times and most of the authors agree that platelets are pathologically activated [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%